Identifikasi Kandungan Organik Dan Logam Berat Sekitar Pabrik Kelapa Sawit Dan Area Bekas Tambang Emas di Sub Das Seminis - Lutfiando, Muhammad Fadli; Gusmayanti, Evi; Akbar, Aji Ali (Universitas Tanjungpura, 2026)
Water quality is a key factor in maintaining ecosystem balance, public health, and the sustainability of the agricultural and industrial sectors. In Sambas District, particularly in the Seminis Sub-watershed, water quality degradation has become a crucial issue, driven by illegal gold mining and the expansion of oil palm plantations, which generate hazardous waste, including mercury, as well as industrial wastewater. This study aims to identify water quality characteristics in the Seminis sub-watershed and analyze the influence of various pollutant sources, particularly from illegal gold mining and oil palm plantations. The research method included surface water sampling at four representative points representing variation in pollutant sources: former mining land, the palm oil mill WWTP outlet, the plantation area, and the settlement. Physical (TSS), chemical (pH, BOD, COD, total nitrogen), and heavy metal (mercury) parameters were analyzed in accordance with national standards and government regulations. The results showed that most water quality parameters remained below the class II quality standards, except for BOD and COD at several points, which exceeded the thresholds due to organic pollutant loads from industrial and agricultural waste.